Green Economy and Public Sector Innovation: A Narrative Review of Global Transitions - Lestari, Putri Ayu (Yayasan Sinergi Kawula Muda, 2025)
This study presents a narrative review of global and local practices in advancing sustainable development through green economy policies, health literacy initiatives, and digital transformation in the public sector. The aim of the review was to synthesize empirical and theoretical contributions to understand the enabling and constraining factors that shape sustainability outcomes. Literature was systematically collected from Scopus, Web of Science, and Google Scholar using keyword combinations such as “green economy,” “health literacy,” and “digital transformation,” with inclusion criteria focusing on peer-reviewed articles published between 2018 and 2024. A total of 126 articles were reviewed after screening 312 records. The results reveal that sustainability has emerged as a central policy and research theme, with evidence showing that green finance, carbon pricing, and stakeholder engagement significantly enhance ecological and economic performance. Comparative insights highlight that developed nations benefit from robust infrastructure and regulatory frameworks, while developing countries face systemic challenges including financial limitations, policy uncertainty, and social inequalities. The discussion underscores the importance of multisectoral collaboration, public education, and fiscal instruments in overcoming these barriers. However, gaps remain in the literature, particularly regarding long-term impacts and the experiences of marginalized populations. The review concludes that advancing sustainable development requires integrative strategies that combine ecological, economic, and social dimensions, with future research needed to explore innovative and inclusive approaches that ensure equitable progress.